Common bile duct stone‐related parameters and their potential prognostic values for stone extraction requiring endoscopic papillary large balloon dilation. Issue 1 (24th November 2022) - Wongkanong, Chote; Patumanond, Jayanton; Ratanachu‐ek, Thawee; Junrungsee, Sunhawit; Tantraworasin, Apichat
Abstract: Background and Aim: For difficult common bile duct (CBD) stones, endoscopic sphincterotomy accompanied by endoscopic papillary large balloon dilatation (EPLBD) may be the preferred initial procedure according to the selection criteria. The purpose of this study was to determine the association between CBD stone‐related parameters and their potential prognostic values for technically difficult CBD stone extraction requiring EPLBD. Methods: We retrospectively analyzed the data of 80 patients who underwent endoscopic retrograde cholangiopancreatography (ERCP), endoscopic biliary sphincterotomy, or the aforementioned procedures combined with EPLBD, resulting in successful CBD stone extraction in the first session from January 2018 and December 2021. The association between CBD stone‐related parameters and stone extraction requiring EPLBD was analyzed by multivariable risk regression analysis. Results: In multivariable analysis, the independent predictors of CBD stone extraction that required EPLBD were CBD stones larger than distal CBD diameter by >2 mm (risk ratio [RR] 2.34, 95% CI 1.30–4.19) and the presence of shaped stones (round shape RR 1.69 [95% CI 1.05–2.73]; square shape RR 2.34 [95% CI 1.24, 4.44] vs oval shape). Conclusion: E ndoscopic CBD stone removal is technically difficult in patients with stones larger than 2 mm in diameter in comparison to the distal CBD diameter or round or square‐shaped stones. Abstract : Endoscopic CBD stone removal is more difficult with stones larger than 2 mm than with distal CBD diameter or round or square‐shaped stones. Therefore, endoscopic large papillary balloon dilatation (ELPBD) is probably more required for stones larger than 2 mm than for distal CBD; likewise, round or square‐shaped stones are likely more required for ELPBD than other shapes.